Investigating Geotourism Capabilities of Geomorphosites in Saymarreh Region Using Pralong Method - Mojtaba Yamani; Samad Azimirad; Sajad Bagheri; Seyed Shakari (جغرافیا و پایداری محیط)
Landforms have high potential in the attraction of geotourism. The relation between landforms and civilization, ancient monuments, historical, cultural as well as sport issues has doubled the capabilities of landforms in the geotourism. Saymarreh region thanks to landforms like Saymarreh Landslide has a high potential in establishing geomorphosites and consequently absorbing the geotourism. The purpose of this study is to assess the capacity of landforms of saymarreh region in attracting the geotourism using the Pralong model. In order to achieve this goal, the Landsat7 ETM 2002 satellite image, topographic maps, geologic maps, digital maps of DEM SRTM 10 meters and ArcGis software have been used as research tools. In this study, firstly geomorphologic landforms with high capability to attract tourism, antiquities and historical monuments, the athletic capabilities of geotourism, accessibility and infrastructures in the region as research variables were examined. Then, we determine scientific, educational and public values of the landforms and identification paper were prepared for recording characteristics of landforms. After that, based on the Pralog model we assessed the geotourism capabilities of the landforms. The research results show that Saymarreh Landslide in average productivity value with a score (0.68) and Sarab e Darehshahr with a score (0.65) has a high potential in the field of geotourism. The Landforms of region, due to high capability in the education of earth science and characteristics such as beauty and being historical, archaeological, cultural and sport attractions, have a high potential in the field of tourism. The main factor of the non-development of geotourism of the region is the lack of infrastructure and appropriate advertisement for it.